Capacity building for critical care training delivery: Development and evaluation of the Network for Improving Critical care Skills Training (NICST) programme in Sri Lanka. (April 2017) - Stephens, Tim; De Silva, A. Pubudu; Beane, Abi; Welch, John; Sigera, Chathurani; De Alwis, Sunil; Athapattu, Priyantha; Dharmagunawardene, Dilantha; Peiris, Lalitha; Siriwardana, Somalatha; Abeynayaka, Ashoka; Jayasinghe, Kosala Saroj Amarasena; et al.
Summary: Objectives: To deliver and evaluate a short critical care nurse training course whilst simultaneously building local training capacity. Research Methodology: A multi-modal short course for critical care nursing skills was delivered in seven training blocks, from 06/2013-11/2014. Each training block included a Train the Trainer programme. The project was evaluated using Kirkpatrick's Hierarchy of Learning. There was a graded hand over of responsibility for course delivery from overseas to local faculty between 2013 and 2014. Setting: Sri Lanka. Main Outcome Measures: Participant learning assessed through pre/post course Multi-Choice Questionnaires. Results: A total of 584 nurses and 29 faculty were trained. Participant feedback was consistently positive and each course demonstrated a significant increase ( p ≤ 0.0001) in MCQ scores. There was no significant difference MCQ scores ( p = 0.186) between overseas faculty led and local faculty led courses. Conclusions: In a relatively short period, training with good educational outcomes was delivered to nearly 25% of the critical care nursing population in Sri Lanka whilst simultaneously building a local faculty of trainers. Through use of a structured Train the Trainer programme, course outcomes were maintained following the handover of training responsibility to Sri Lankan faculty. The focus on local capacity building increases the possibility of long term course sustainability.